Notes from the Editor - Jose, Ricardo T. (Kasarinlan: Philippine Journal of Third World Studies, 2017)
Notes from the Editor and Program Leader, Special Supplement from the EIDR Research Program "The Mass Transit System in Metro Manila: From Tranvia to MRT, 1879–2014"